Differential Retention and Loss of a Mycotoxin in Fungal Evolution - Lin Chen; Ziying Yan; Bolei Yang; Bowen Tai; Weizhao Li; Erfeng Li; Gang Wang; Fuguo Xing (Toxins, 2025)
Ochratoxin A (OTA) is designated as a mycotoxin and is regulated worldwide due to its harmful effects on humans and animals, but the evolutionary history and ecological significance of OTA in fungi remain poorly understood. Phylogenetic analysis suggested that Aspergillus and Metarhizium obtained an ancient OT cluster, which evolved independently, followed by horizontal OT transfer from Aspergillus to Penicillium. The varying presence of functional, absent and pseudogenized OT genes across Aspergillus species revealed that this cluster is undergoing a degeneration process in this genus. Furthermore, the cyclase OtaY in the OTA cluster is likely derived from bacteria, which was revealed by phylogenetic analysis. This is the first attempt to investigate the ecological significance of OTA in fungi, suggesting that it may be nonfunctional in Aspergillus spp. and has undergone multiple forms of loss during evolution.